Learners’ Vocabulary and Conceptual Understanding of Selected Physical Science Words - Alcarde, Joylin (International Journal of Education, Research, and Innovation Perspectives, 2026)
This action research examined the effectiveness of a vocabulary-focused intervention in improving the vocabulary mastery and conceptual understanding of selected Physical Science words among 35 Grade 12 Technical-Vocational-Livelihood (TVL) learners in the Automotive Servicing and Home Economics strands. Purposefully sampled due to observed difficulties in recognizing, pronouncing, and defining scientific terms, the participants underwent an intervention consisting of a Science Word Bank, vocabulary drills, concept reinforcement activities, and interactive tools integrated into regular instruction. The study employed a classroom action research design utilizing a teacher-made pretest and post-test, alongside qualitative tools including perception questionnaires, classroom observations, and learner reflections. Quantitative findings revealed a statistically significant increase in mean scores from 12.63 in the pretest to 17.03 in the post-test, yielding a mean gain of 4.40 points, t(34) = 7.49, p < .001. Learners evaluated the intervention highly positively with an overall perception mean of 4.90, while classroom observations confirmed active participation with a mean of 3.92. Thematic analysis of qualitative data substantiated these results, showcasing marked improvements in vocabulary development, conceptual understanding, real-life application, and classroom engagement. The study concludes that explicit, contextualized, and interactive vocabulary instruction effectively bridges learning gaps and enhances academic performance. Continued integration of vocabulary-focused strategies is highly recommended for Physical Science and other technical courses where specialized terminology poses a barrier to learner comprehension.